Influence of K2NbF7 Catalyst on the Desorption Behavior of LiAlH4 - Ali, Nurul Amirah; Sazelee, Noratiqah; Yahya, Muhammad Syarifuddin; Ismail, Mohammad (Frontiers in Chemistry, 2020)
In this study, the modification of the desorption behavior of LiAlH4 by the addition of K2NbF7 was explored for the first time. The addition of K2NbF7 causes a notable improvement in the desorption behavior of LiAlH4. Upon the addition of 10 wt.% of K2NbF7, the desorption temperature of LiAlH4 was significantly lowered. The desorption temperature of the LiAlH4 + 10 wt.% K2NbF7 sample was lowered to 90°C (first-stage reaction) and 149°C (second-stage reaction). Enhancement of the desorption kinetics performance with the LiAlH4 + 10 wt.% K2NbF7 sample was substantiated, with the composite sample being able to desorb hydrogen 30 times faster than did pure LiAlH4. Furthermore, with the presence of 10 wt.% K2NbF7, the calculated activation energy values for the first two desorption stages were significantly reduced to 80 and 86 kJ/mol; 24 and 26 kJ/mol lower than the as-milled LiAlH4. After analysis of the X-ray diffraction result, it is believed that the in situ formation of NbF4, LiF, and K or K-containing phases that appeared during the heating process promoted the amelioration of the desorption behavior of LiAlH4 with the addition of K2NbF7.